Weather and Climate Resilience : Effective Preparedness through National Meteorological and Hydrological Services - Rogers, David P.; Tsirkunov, Vladimir V. (Washington, DC: World Bank, 2013)
The importance of weather, climate, and water1 information is rising because of the need to serve more elaborate societal needs, minimize growing economic losses, and help countries adapt to climate change. Weather, climate, and water affect societies and economies through extreme events, such as tropical cyclones, floods, high winds, storm surges, and prolonged droughts, and through high-impact weather and climate events that affect demand for electricity and production capacity, planting and harvesting dates, management of construction, transportation networks and inventories, and human health. The key players are the National Meteorological and Hydrological Services (NMHSs), which are the backbone of the global weather and climate enterprise. By international agreement under the auspices of the World Meteorological Organization (WMO), they are the government's authoritative source of weather, climate, and water information, providing timely input to emergency managers, national and local administrations, the public, and critical economic sectors. The report underscores the urgent need to strengthen NMHSs, especially those in developing countries, and provides cost-benefit estimates of the return that countries can hope to achieve. It also offers a recommended approach that has been tested and implemented in Europe, in Central and South Asia, and countries in other regions. The NMHSs make a significant contribution to safety, security, and economic well-being by observing, forecasting, and warning of pending weather, climate, and water threats.